The Role of Internal Audit, Code of Ethics, and Independence on Audit Quality (Case Study at the Inspectorate Office of Banten Province in 2022) - Susana Dewi; Humairoh As Salma; Karsam; Paniran; Herlina (Indonesian Journal of Economic & Management Sciences, 2023)
In order to realize good governance, which is like good governance, it is hoped that regional governments can increase transparency, accountability, and fairness in regional financial management. This study aims to analyze the role of internal audit on audit quality, the role of a code of ethics on audit quality, independence on audit quality and the influence of the role of internal audit, code of ethics and independence on audit quality. This research uses quantitative methods. The population used in this study were 67 respondents/auditors in the Insectorate Office of Banten Province. Sampling used a purposive sampling method using primary data, the primary data in this study was in the form of data from questionnaires distributed. Research data were analyzed using multiple linear regression analysis with the help of SPSS version.25. The results of this study found that Internal Audit has no partial effect on Audit Quality, the Code of Ethics and Independence has a partial effect on Audit Quality. Internal Audit, Code of Ethics and Independence simultaneously have a positive and significant effect on Audit Quality